Comparative Study of Fatty Acids and Triglycerids of Luffa cylindrica Versus Cucurbitaceae Seeds Consumed in Congo Brazzaville - Tsieri, M. Mvoula; Niamayoua, R. Kama; Mampouya, D.; Silou, Th.; Tremolieres, A.; Heron, S.; Tchapla, A. (Pakistan Journal of Nutrition, 2008)
Fatty acids composition of various classes of lipids (neutral and polar lipids) was determined by gas chromatography (GC) and triacylglycerols (TAG) composition by high performance liquid chromatography (HPLC). The comparative study of fatty acids and triacylglycerols composition of the five cucurbitaceae species analyzed allow similarities within the species. The essence of the linoleic acid C 18:2 are concentrated in the TAG and the acids linoleic C 18:3 and palmitoleic C 16:1 can be used as factor discriminating the studied species.